Circulating MicroRNAs and myocardial involvement severity in chronic Chagas cardiomyopathy - Gómez-Ochoa, Sergio Alejandro; Bautista-Niño, Paula Katherine; Rojas, Lyda Z.; Hunziker, Lukas; Muka, Taulant; Echeverría, Luis E. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Chronic Chagas Cardiomyopathy (CCM) is characterized by a unique pathophysiology in which inflammatory, microvascular and neuroendocrine processes coalesce in the development of one of the most severe cardiomyopathies affecting humans. Despite significant advances in understanding the molecular mechanisms involved in this disease, scarce information is available regarding microRNAs and clinical parameters of disease severity. We aimed to evaluate the association between circulating levels of six microRNAs with markers of myocardial injury and prognosis in this population. Methods: Patients with CCM and reduced ejection fraction were included in a prospective exploratory cohort study. We assessed the association of natural log-transformed values of six circulating microRNAs (miR-34a-5p, miR-208a-5p, miR-185-5p, miR-223-5p, let-7d-5p, and miR-454-5p) with NT-proBNP levels and echocardiographic variables using linear regression models adjusted for potential confounders. By using Cox Proportional Hazard models, we examined whether levels of microRNAs could predict a composite outcome (CO), including all-cause mortality, cardiac transplantation, and implantation of a left ventricular assist device (LVAD). Finally, for mRNAs showing significant associations, we predicted the target genes and performed pathway analyses using Targetscan and Reactome Pathway Browser. Results: Seventy-four patients were included (59% males, median age: 64 years). After adjustment for age, sex, body mass index, and heart failure medications, only increasing miR-223-5p relative expression levels were significantly associated with better myocardial function markers, including left atrium area (Coef. -10.2; 95% CI -16.35; -4.09), end-systolic (Coef. -45.3; 95% CI -74.06; -16.61) and end-diastolic volumes (Coef. -46.1; 95% CI -81.99; -10.26) of the left ventricle. Moreover, we observed that higher miR-223-5p levels were associated with better left-ventricle ejection fraction and lower NT-proBNP levels. No associations were observed between the six microRNAs and the composite outcome. A total of 123 target genes for miR-223-5p were obtained. From these, several target pathways mainly related to signaling by receptor tyrosine kinases were identified. Conclusions: The present study found an association between miR-223-5p and clinical parameters of CCM, with signaling pathways related to receptor tyrosine kinases as a potential mechanism linking low levels of miR-223-5p with CCM worsening.